1996
DOI: 10.1126/science.274.5288.784
|View full text |Cite
|
Sign up to set email alerts
|

TNF- and Cancer Therapy-Induced Apoptosis: Potentiation by Inhibition of NF-κB

Abstract: Many cells are resistant to stimuli that can induce apoptosis, but the mechanisms involved are not fully understood. The activation of the transcription factor nuclear factor-kappa B (NF-kappaB) by tumor necrosis factor (TNF), ionizing radiation, or daunorubicin (a cancer chemotherapeutic compound), was found to protect from cell killing. Inhibition of NF-kappaB nuclear translocation enhanced apoptotic killing by these reagents but not by apoptotic stimuli that do not activate NF-kappaB. These results provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

83
1,755
13
9

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,489 publications
(1,860 citation statements)
references
References 36 publications
83
1,755
13
9
Order By: Relevance
“…32 Similarly, transfection of a dominant negative form of IkBa complememtary DNA (cDNA) (IkBa-DN) prevented the TNF-induced cell death. 33,34 A sustained level of IKKs is required for constitutive activation of NF-kB. 35,36 Although BAY completely inhibited IKK activity in NF-kB-expressing cells, it showed 30% cell death alone at 72 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, transfection of a dominant negative form of IkBa complememtary DNA (cDNA) (IkBa-DN) prevented the TNF-induced cell death. 33,34 A sustained level of IKKs is required for constitutive activation of NF-kB. 35,36 Although BAY completely inhibited IKK activity in NF-kB-expressing cells, it showed 30% cell death alone at 72 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gel mobility shift assay revealed that TNF-ainduced nuclear translocation of NF-kB was blocked in RR/DN-IkBa-H cells ( Figure 3a). In addition, consistent with recent observations that NF-kB activity is required for TNF-a-induced cell death in various cell types (Antwerp et al, 1996;Beg and Baltimore, 1996;Liu et al, 1996;Wang et al, 1996), TNF-a treatment in RR/DN-IkBa-H cells led to a massive cell death within 18 h, whereas parental Rat-1(Ras) and RR/DNIkBa-L cells were little a ected ( Figure 3b). The genomic DNA isolated from RR/DN-IkBa-H cells after TNF-a treatment also exhibited a characteristic DNA fragmentation and corresponding cytoplasmic extract was shown to be capable of activating procaspase-3 ( Figure 3c).…”
Section: Inactivation Of Nf-kb Leads To Growth Inhibition and Reducedsupporting
confidence: 91%
“…It was suggested that oncogenic proteins, by modulating the activity of downstream transcription factors, may activate a set of genes which inhibit transformationassociated apoptosis (Koumenis and Giaccia, 1997). NF-kB has been shown to play an important role in protection from cell death, presumably by regulating the expression of anti-apoptotic genes (Antwerp et al, 1996;Beg et al, 1996;Liu et al, 1996;Wang et al, 1996;Chu et al, 1997;Yamit-Hezi and Dikstein, 1998;You et al, 1997). In light of these observations, it has been reported that Ras activates NF-kB to prevent transformation-mediated cell death and this antiapoptotic activity of NF-kB may be important for Ras-mediated cell transformation and tumorigenesis (Mayo et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…According to several recent studies, NF-kB and p53 have antagonistic roles in the control of apoptosis in response to DNA damage. Indeed, NF-kB activation by daunomycin, camptothecin or ionizing radiations inhibits apoptosis through the transactivation of antiapoptotic genes (Van Antwerp et al, 1996;Wang et al, 1996Wang et al, , 1999. Moreover, it has been reported that NF-kB prevents p53-dependent transactivation through a competition for the coactivators p300 and CBP (Ravi et al, 1998;Wadgaonkar et al, 1999;Webster and Perkins, 1999).…”
Section: Discussionmentioning
confidence: 99%